Pengaruh Customer Perceived Value , Service Quality, Dan Physical Environment Terhadap Kepuasan Dan Kesetiaan Pelanggan - Shelly Agustina Natawijaya; Keni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2018)
The aim of this study are : First, to explore the effect of customer perceived value , service quality, and physical  environment on customer loyalty. Second, to explore the effect of  customer perceived value , service quality, and physical  environment on customer satisfaction. Third, to explore the effect of customer satisfaction towards customer loyalty. Fourth, to find out if customer satisfaction can mediate  customer perceived value , service quality, and physical  environment towards customer loyalty.  The method of data collection is purposive sampling.  The samples of this research are collected from 326 respondents, who are the customers of  furniture store in Jakarta.  The technique of data analysis used in this study was regression analysis and mediating test to find put the hypotheses. The results are : (a) the relationship between customer perceived value , service quality, and physical  environment have a significant and positive impact toward customer loyalty; (b)  the relationship between customer perceived value , service quality, and physical  environment have a significant and positive impact toward customer satisfaction; (c) customer satisfaction has a positive impact on customer loyalty; (d) customer satisfaction  will mediate the effect of  customer perceived value , service quality, and physical  environment towards customer loyalty.